KONTEKSTUALISASI AYAT-AYAT ‘IDDAH - Firiana Firdausi (AL-TADABBUR, 2019)
Until now, ‘iddah for some women has been a dilemma. The dilemma is because some obligations that must be undertaken by a mu’taddah seem to limit a woman’s self actualization, within a certain period of time. Prohibition of leaving the house (QS. 65:1) may be a very severe consequence for mu’taddah today. This article tries to understand verses relating to ‘iddah using the perspective of Abdullah Saeed’s contextual theory. Institutionalization of ‘iddah, in its historical context, is an effort to protect and provide justice to women. Finally, what must be considered, according to Saeed, is the fundamental value of verse, not the instructional value.